Life expectancy in HIV-infected individuals after the start of antiretroviral therapy - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
According to a new study, the life expectancy of HIV-infected people after the start of ART for the last 2 decades has increased significantly.